Research on Space-Ground Network Security Guarantee Technology - Fenghua LI; Linjie ZHANG; Yueming LU; Kui GENG; Yunchuan GUO (天地一体化信息网络)
The characteristics of space-ground network was combed.Against security threats in space-ground network,the security risks faced by measurement control,operation control,terminal access,wireless transmission,transmission,business information system,maintenance management were analyzed.Further,by dividing space-ground network security into four layers:foundation layer,access layer,network layer and application layer,a security architecture to protect space-ground network was proposed.An implement mechanism (including unifi ed security management and security situation aware,entity authentication and access protection,interconnection control,cipher on-demand service,dynamic reconstruction of security service ) was designed to guarantee the security of space-ground network.